Linfoma pulmonar MALT: reporte de un caso y revisión de la literatura - Carolina Amado; Tiago Valente; Gisela Ferreira; Margarida Cruz (Sociedade Galega de Medicina Interna, 2023)
Pulmonary mucosa-associated lymphoid tissue lymphoma (pMALToma) is an extranodal low-grade B-cell lymphoma which originates from bronchial and/or parenchyma MALT. The authors report a case of an 81-year-old female with incidental finding of multiple bilateral pulmonary consolidations. After being submitted to an extensive workup, the diagnosis of pMALToma was finally established. The authors intend to highlight this rare entity and its challenging workup. It Is characterized by non-specific clinical manifestations and diverse imaging findings frequently leading to the need to perform more invasive techniques for a final diagnosis.